2018
DOI: 10.17648/sinergia-2236-7608-v22n2-7529
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores De Desempenho Em Serviços E Produção: Proposta De Mapeamento Da Produção Científica À Luz Da Bibliometria

Abstract: O presente trabalho tem como objetivo caracterizar a produção científica referente aos indicadores de desempenho em serviços e produção no período compreendido entre 2007 e 2017, utilizando-se a bibliometria para realizar estudos na produção, no que refere à autoria, ao conteúdo e às referências dos artigos selecionados, por meio da análise de artigos disponíveis em bases de dados online. Metodologicamente, o estudo é de natureza exploratória, porquanto adota a revisão bibliográfica dos artigos. Foram buscados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…It is observed that it is essential to define performance indicators to carry out an adequate assessment, as they are items that assist in management and control, necessary to understand whether the objectives proposed by the organization were achieved, thus supporting the decisionmaking process (Oliveira et al, 2020). Its definition also provides better knowledge about products and services (Pereira Junior et al, 2018), and when aligned with organizational objectives, they lead to improvement initiatives in the short, medium, and long term, which subsidize the changes in a sustainable way, being the basis for the organizational strategy (Bassi et al, 2020).…”
Section: Organizationmentioning
confidence: 99%
“…It is observed that it is essential to define performance indicators to carry out an adequate assessment, as they are items that assist in management and control, necessary to understand whether the objectives proposed by the organization were achieved, thus supporting the decisionmaking process (Oliveira et al, 2020). Its definition also provides better knowledge about products and services (Pereira Junior et al, 2018), and when aligned with organizational objectives, they lead to improvement initiatives in the short, medium, and long term, which subsidize the changes in a sustainable way, being the basis for the organizational strategy (Bassi et al, 2020).…”
Section: Organizationmentioning
confidence: 99%